Peningkatan Pemahaman Literasi Keuangan dan Investasi Bodong Melalui Seminar Pendidikan - Muh Wiswandi Murlan; Muhamad Bighta Pratiya; Aditya Rifki Putra; Mentari Syafar; Ady Adriansyah; Rezky Ramadhan; Muhammad Irfai Sohilauw (Forum Kerjasama Pendidikan Tinggi, 2023)
The low level of financial literacy and the rise of fraudulent investments have targeted the rural level, including in Panaikang Village, Pattalassang District, Gowa Regency, and South Sulawesi. From the initial identification and survey results, villagers still need to understand financial literacy. Apart from that, residents are still tempted by the bulging investments offered. This seminar aims to increase the financial literacy of Panaikang village residents. In addition, this seminar also provides tips to avoid fraudulent investments that are rife. The methods used are educational seminars and discussions. The participants' understanding of financial literacy and fraudulent investment increased from the pre and post-test evaluations.